Influência dos cenários de prática e preceptoria na formação médica - Cavalcante, Ana Neiline (2024)
Higher education in the health sector has been undergoing major changes in the context of health professional training. The National Curricular Guidelines recommend that medical training be generalist, humanist, critical and reflective, based on ethical principles, in order to make the professional capable of acting in the health-disease process in different scenarios and levels of care, with an emphasis on actions that directly affect the problems or needs identified in the community. In this sense, the general objective of this thesis is to understand the influence of practice scenarios and their actors on the academic path and the formation of the medical student's professional identity; as specific, identify the influence of practice scenarios on medical training and the medical student's professional identity and describe the influence of the student preceptor relationship on medical training and the medical student's professional identity. This is a qualitative, exploratory and descriptive study, carried out at a Higher Education Institution in the city of Ceará, with the participation of 25 students, covering the first, fourth and eighth semesters, whose data collection took place in the months of August and September, from 2023, by carrying out three focus groups. The results were subjected to content analysis in the thematic modality, following the steps recommended by this analytical modality, originating the categories and subcategories: (i) Academic training, unfolding in preparation for practice, lack of theoretical knowledge for practice and theoretical content versus practice; (ii) technicality view; (iii) training in practice scenarios, encompassing the preceptor's contribution, stimulation of learning and concern for the future. The research results show that coexistence and immersion in health care practice fields contribute to directing the student's interest in the specialties and their procedural and technological devices. It also shows the influence of preceptors who constitute an inspiration and model for doctors in the future, as well as the need for preparation for general practitioners. In summary, it is considered that situations have emerged that demand reorientations in pedagogical practice, strengthening bonds between students and preceptors and expanding dialogical communication between peers, teachers and the actors that make up the practice scenarios and the real world. Keywords: Medical Education; Practice Scenarios; Medical Students; Preceptorship.